Meaning of countertransference in a music therapy student's clinical studies - towards a professional perspective - Savela, Tiinapriitta (2013)
The concept of countertransference refers to the therapist's reactions to the client's inner world in therapy situation. Countertransference within therapy relationships can alternate from the therapist's obstructive reactions to positive experiences that may even guide the therapist towards purposeful interventions. In this research I study my own countertransference experience and my learning process of the meaning of countertransference. The methodology of the research is hermeneutic phenomenology and its structure follows the principles of the hermeneutic circle and of Gadamerian hermeneutic analysis. The data is composed of my self-reflections. I examine the self-reflections in the light of background theories that I have chosen to guide the analytical process. I analyze my reactions in therapy situation and the countertransference triggers that the situation contains, first by applying the countertransference theories of the psychodynamic frame of reference, then by considering the significance of music and musical interaction for my countertransference, and eventually by discussing the influence of my countertransference on the interaction within the therapy relationship. The content analysis proceeds as a dialog between the data and the literature, which eventually leads to a deeper understanding of the experience. Through this research process, I have learnt to observe the complex constructions of countertransference experiences in therapy relationships. I have also understood the importance of countertransference experiences in a student's personal growth and in the attainment of the goals set in music therapy training. As a result, I have formulated a tool for uncovering and processing countertransference. I now use this tool in my music therapy work and put the new understanding into practice.